Zero rating and capacity investment - Monteiro, Francisco José Ramos (2018)
This paper analysis zero-rating, a practice where Mobile Network Operators (MNOs) exclude some traffic from being charged when consumers use mobile broadband data. Focusing on the downstream effects and considering two competing firms, two contents and network effects (externality) on one of the contents, it is shown that zero-rating can be used to increase, and thereafter, extract more surplus from consumers, when network effects are strong enough. Moreover, it is shown that the interaction between contents has an impact on investment decisions, as substitutes contents lead to lower investment when the network effect increases while complementary contents result in higher investment for stronger network effects. Finally, zerorating can lead to higher network capacity than under joint billing, when investment costs are high enough.